(untitled) (Proceedings of the International Conference on Education, 2025)
The pedagogical methods used in music education play a crucial role in students’ learning outcomes, including creativity and artistic expression, musical knowledge and theory, performance skills, technical proficiency, and more. A decline in these outcomes is often observed among music students, potentially due to the pedagogical methods engaged. This study explores the relationship between pedagogical methods and learning outcomes, focusing on the impact of traditional and modern approaches. Data was collected using mixed methods from 250 students (grades 6 to 11) and 20 teachers in the Western Province, through interviews, surveys, focus group discussions, and classroom observations. Comparative analysis of traditional methods, such as rote memorization and teacher-directed instruction, and modern techniques, including collaborative projects, experiential learning, and technological integration, revealed a significant relationship between active, student-centered teaching methods and improved learning outcomes. Quantitative data showed enhanced engagement and performance levels, while qualitative findings highlighted the importance of innovative, context-specific practices. However, insufficient resources and limited teacher training emerged as key barriers to fully realizing the benefits of innovative practices. The findings support a hybrid instructional model that combines traditional and modern techniques, preserving the cultural integrity of music while addressing the dynamic educational needs of learners. Recommendations for future research include strategies to address these barriers and further exploration of hybrid pedagogical models in diverse educational contexts.